Ketimpangan Distribusi Pendapatan dan Faktor-Faktor yang Mempengaruhinya di Kabupaten Purbalingga - Lilis Badriah; Herman Sambodo; Irma Suryahani (EKO-REGIONAL, 2006)
The purposes of this research are to analyze level of inequality income distribution and factors influencing per capita income change in Purbalingga. The research method of this research is case study with descriptive analysis  using secondary data include per capita income,  amount of population,  economic sectoral contribution to GDRP of Purbalingga,  and development expenditure during 1990-2003.  To analyze level of inequality income distribution it use Williamson Index Analysis method.  The results of this research indicate that: 1) Average of Williamson Index value during 1990-2003 is 0.07 » 0.1. 2) Simultaneously, amount of population, primary sector contribution, secondary sector contribution, tertiary sector contribution, and development expenditure have a significant effect to per capita income change.  Partially, amount of population, primary sector contribution, secondary sector contribution, and tertiary sector contribution have a significant effect with regression coefficient value for each variable is 4,809, 12,007, 4,511, and 15,273. While development expenditure is not having a significant effect to per capita income change. The conclusions of this research are level of inequality income distribution in Purbalingga during 1990-2003 is low inequality income distribution category, and per capita income change is influenced significantly by amount of population, primary sector contribution, secondary sector contribution, and tertiary sector contribution.  The tertiary sector contribution has a biggest influence.Keywords: inequality income distribution, per capita  income  change, government expenditure